Comparative Study of Fatty Acids Profiles in Mangifera indica L. Seed Butter Extracts from Different Regions in Nepal Using GC-MS - Bhatta, Indu; Shrestha, Prabina; Acharya, Prajwal; Pantha, Sabina; Devkota, Rojina; Adhikari, Achyut (Journal of Plant Resources, 2025)
Mango is widely consumed for its pulp; however, the kernels are often discarded as a waste product despite their potential application. This research aims to study the potential application of the kernel in the production of butter. The study involves chemical profiling of butter extracted from kernels of mango collected from various regions of Nepal for their possible application in the confectionery industry as a cocoa butter replacement. Samples were collected from different districts, including Bardiya, Doti, Kathmandu, Tanahun, and Dhangadhi. The collected samples were cleaned, dried, and ground into powder. Butter was extracted employing the Soxhlet extraction technique using n-hexane as a solvent. The extracted mango seed butter was then analyzed using Gas Chromatography- Mass Spectrometry (GC-MS) to determine the fatty acid composition. Despite species-specific variations in concentration, octadecanoic acid (stearic acid), a crucial component of mango seed butter, was the most consistently found chemical in the samples studied. Some other important fatty acids such as oleic acid and palmitic acid were also present in the kernel of mango.